ANATOMY OF LANGUAGE AND THEORETICAL ASSUMPTIONS OF COGNITIVE SCIENCE, COMPARATIVE ANALYZES - Achilov, Oybek (Журнал иностранных языков и лингвистики, 2023)
The studying of language layers and its anatomy is very actual to distinguish further information on cognitive science, therefore in this article, it has been analyzed and covered points interrelated to research cognitive science with cognitive meaning.